Improving transaction abort rates without compromising throughput through judicious scheduling - Pereira, José (2013)
Althought optimistic concurrency control protocols have increasingly been used in distributed database management systems, they imply a trade-of between the number of transactions that can be executed concurrently, hence, the peak throughput, and transactions aborted due to conflicts. We propose a novel optimistic concurrency control mechanism that controls transaction abort rate by minimizing the time during which transactions are vulnerable to abort, without compromising throughput. Briefly, we throttle transaction execution with an adaptive mechanism based on the state of the transaction queues while allowing out-of-order execution based on expected transaction latency. Prelimi- nary evaluation shows that this provides a substantial improvement in committed transaction throughput.